FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENCEGAHAN HIV/AIDS PADA REMAJA DI KOTA DEPOK TAHUN 2022 - Aulia Zikry Bunga Mentari, (2022)
HIV/AIDS is a global health problem. The long-term effects of HIV / AIDS without treatment can weaken the body so that it is easy to get opportunistic infections that can cause death. The high rate of HIV infection in Depok City makes good HIV / AIDS prevention behaviors needed. This study aims to see what factors influence HIV / AIDS prevention behavior in adolescents in Depok City. This study used a cross-sectional study design with a total sample of 304 people. Data collection was carried out in June 2022 using an online questionnaire. The dependent variables in this study were HIV / AIDS prevention behaviors with nine independent variables, namely age, gender, occupation, education, income, knowledge, attitudes, access to information on peer roles. The analysis starts from univariate, bivariate analysis using chi square, as well as multivariate analysis using multiple logistic regression tests. Multivariate analysis, educational factors (POR 5.09, 95% CI: 1.18-22.00) are the most dominant determinants associated with HIV/AIDS prevention behaviors. It is recommended to provide more centralized education to population-at-risk but still sustainable groups.